Pemberian Edukasi dan Praktek Personal Hygiene dalam Meningkatkan PHBS pada Remaja di SMPN 5 Sumbawa Besar - Meliana Fitri; Lina Eta Safitri; Nur Arifatus Sholihah; Putri Adekayanti (Jurnal Nusantara Berbakti, 2025)
Personal hygiene is an action to maintain a person's cleanliness and health for physical and psychological well-being, lack of self-care is a condition where a person is unable to perform hygiene care for themselves. Based on the results of observations and interviews, information was obtained that students of SMPN 5 Sumbawa Besar did not understand about caring for a clean and healthy life and how to implement good Personal Hygiene. At the age of adolescence, school children need to be given education related to personal hygiene, but these students have never received such education, therefore based on the background above, the activity of providing personal hygiene education in improving PHBS was conveyed to the community, especially school teenagers. This community service aims to provide students with an understanding of the importance of maintaining personal hygiene in improving PHBS at SMPN 5 Sumbawa Besar. This activity is carried out through providing education using booklets and PPT related to the material presented, in the final stage students will be given a question and answer session, the results of the community service show that students' understanding before and after the provision of education and practice has increased and students are very enthusiastic in answering questions.